Persepsi Guru dalam Penggunaan Media Pembelajaran Digital pada Puisi Tradisional: Teachers' Perceptions in the Use of Digital Learning Media in Traditional Poetry - Nurjihaan Nabiilah; Suyono Suyono; Gatut Susanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to identify: (1) teachers’ perceptions of the importance of using digital learning media in traditional poetry learning, (2) the types of digital learning media used by teachers, and (3) the obstacles faced in implementing it in the school environment. This study used a quantitative, survey-based approach. Data were collected using a dichotomous-scale questionnaire distributed to 30 Indonesian language teachers in junior high schools. The results showed that teachers’ perceptions of the use of digital learning media were in the very positive category. This was indicated by the high percentages in the cognitive (98.6%), affective (97.2%), and conative (81.1%) aspects. These findings indicate that teachers have a good understanding, supportive attitudes, and a tendency to apply digital media in traditional poetry learning. However, this study also found several obstacles to implementing digital learning media, with a 66% rate. These obstacles include limited availability of digital media relevant to the learning material, differences in students’ abilities to access and use technology, and limited time during classroom instruction. Thus, digital learning media have great potential to improve the quality of learning traditional poetry. Therefore, support is needed by providing adequate facilities and infrastructure, improving teachers’ digital competencies, and managing learning time more effectively, so that implementation can run optimally and sustainably.